Essential writings of Sudhir Kakar - Kakar, Sudhir (New Delhi Oxford Unoversity Press, 2001)
This book focuses for the first time on a living writer, as part of Essential Writings series,is indispensable for a psychological understanding of the country as it establish itself in this millennium. It is meant for students of psychology, South Asian
Keywords: Culture; Sociology